Approaches for Delineating Groundwater Recharge Potential Zone Using Fuzzy Logic Model. (14th November 2022) - Haile, Mesfin Mamo
Abstract : Groundwater recharge potential is an important spatial analysis to refer where the groundwater recharge is likely to happen. The present study discusses approaches for determining groundwater recharge potential zones in the Guder watershed, Ethiopia, using geospatial and fuzzy logic techniques on derived thematic layers based on significant influence of groundwater occurrence. A variety of thematic layers were created using satellite images and other ancillary data, including drainage density, slope, rainfall, geology, land use/land cover, lineament density, soil, and geomorphology. Researchers, expert opinion, and previous studies were used to estimate the membership value for each governing factors. According to the findings of the study, approximately 5.25% of the area has very high groundwater recharge potential, and 9.34% of the area has high groundwater recharge potential, while the areas with very low, low, and moderate groundwater recharge potential are approximately 20.04%, 34.21%, and 31.15%, respectively. The study's findings were confirmed by looking at the cross-tabulation area between the contributing features and the final map, which demonstrated strong associations. The findings of the study will help decision-makers and policymakers plan to implement appropriate groundwater recharge procedures. Fuzzy logic approaches have been found to be a basic tool for estimating groundwater recharge locations when used with GIS.